Hypomutability in Fanconi anemia cells is associated with increased deletion frequency at the HPRT locus. - Papadopoulo, D (1990)
Fanconi anemia (FA) is an inherited human disorder associated with a predisposition to cancer and characterized by anomalies in the processing of DNA cross-links and certain monoadducts. We reported previously that the frequency of psoralen-photoinduced mutations at the HPRT locus is lower in FA cells than in normal cells. This hypomutability is shown here to be associated with an increased frequency of deletions in the HPRT gene when either a mixture of cross-links and monoadducts or monoadducts alone are induced. Molecular analysis of mutants in the HPRT gene was carried out. In normal cells the majority of spontaneous and induced mutants are point mutations whereas in FA deletion mutations predominate. In that case a majority of mutants were found to lack individual exons or small clusters of exons whereas in normal cells large (complete or major gene loss) and small deletions are almost equally represented. Thus we propose that the FA defect lies in a mutagenic pathway that, in normal cells, involves bypassing lesions and subsequent gap filling by a recombinational process during replication.